Poppy's return - Avi, 1937-; Floca, Brian (New York : HarperCollins Publishers, 2005)
Poppy, accompanied by her troublesome son Junior, his skunk friend, and Uncle Ereth the porcupine, responds to a summons to return to her ancestral home, Gray House, to save the mice there from destruction by a bulldozer.
Book Links (A.L.A.).
Horn Book.
Kirkus Review.
4.1
3-6
570L
Keywords: Family problems -- Fiction; Prejudices -- Fiction; Mothers and sons -- Fiction; Mice -- Fiction; Skunks -- Fiction; Porcupines -- Fiction; Family problems -- Fiction; Prejudices -- Fiction; Mother-son relationship -- Fiction